Reconstructing the Epistemology of Islamic Religious Education: Integrating Naṣr Ḥāmid Abū Zayd’s Hermeneutics with the Love-Based Curriculum - Muhdi Ali; Ade Fakih Kurniawan; Iffan Ahmad Gufron (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
The teaching of Islamic Religious Education (PAI) is still dominated by an epistemological framework that positions religious texts as fixed and closed sources of meaning, so that learning practices tend to be reduced to the transmission of interpretations. Previous studies generally focused on pedagogical aspects, without examining the epistemological assumptions underlying the way texts are understood. This study aims to reconstruct the epistemology of PAI learning through Naṣr Ḥāmid Abū Zayd’s hermeneutics and the maʿnā–cum–maghzā approach within the context of a Love-Based Curriculum. This research employs a qualitative approach based on text analysis with a philosophical hermeneutical framework. The primary data come from Abū Zayd's works (Mafhūm al-Naṣṣ and Naqd al-Khiṭāb al-Dīnī), which are analyzed through textual identification, conceptual extraction, and hermeneutical interpretation, and then mapped comparatively with the maʿnā–cum–maghzā methodology. The research findings indicate that (1) the Qur’an is constructed as a historical-linguistic discourse formed in a dialectical relationship with social reality; (2) revelation functions as a communicative process involving text, context, and the reader; and (3) the distinction between al-maʿnā and al-maghzā serves as an epistemological mechanism that enables a balance between the reconstruction of historical meaning and the production of contextual significance. Based on these findings, the study identifies an epistemological shift from a transmission-based learning model toward a dialogical-interpretative process that positions learners as active epistemic subjects. These findings imply that without an epistemological reconstruction, value-based approaches such as the Love-Based Curriculum risk remaining merely affective, making the integration of Abū Zayd’s hermeneutics crucial for developing reflective and contextual Islamic Religious Education (PAI) learning